Magill's cinema annual 2015 a survey of the films of 2014 - Tallerico, Brian (Gale virtual reference library, 2015)
Offers an in-depth retrospective of significant domestic and foreign films released in the United States during the preceding year. Distinguishing features include its extensive credits, awards and nominations, MPAA ratings, thorough indexes, and its exhaustive critical reviews with author bylines.